Therapeutic Strategy for Recurrent Ulcerative Colitis - Pranata, Anak Agung Ngurah Satya; Wirawan, I Made Suma; Kumala Dewi, Anak Agung Istri Sri; ., Novitasari (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Ulcerative Colitis (UC) is a chronic idiopathic inflammation that appears from the rectum and can extend to colon causing diffuse friability and superficiality. In this case report, Woman, 44 years old, admitted to hospital because of bloody diarrhea, frequency of 4-6 times daily with mucous, malaise, and history of weight loss. Patient already had oral sulfasalazine and oral corticosteroid to maintain her condition, but she stopped the medication at will. On physical examination, showed anemic conjunctiva and increasing in bowel sound, fecal examination showed brown to red, porridge-like consistency, blood, mucous, and positive Benzidine test. Colonoscopy examination revealed, normal anus; in the sigmoid rectum, colon descendent found small swellings, an ulcer, and few bloody. On histopathology, epithelial surface with mucin depletiondistortion of crypt architecture, dilatation and elongation of crypt, as well as shortening of the crypt that does not reach muscular mucous and lamina propria contains solid aggregate inflammation cells, dominated by plasma cells. The patient was given  combination of 5-aminosalicylates and glucocorticoids. On re-evaluation in week 8 of therapy, frequency of defecation becomes 1-2 times daily with no blood occurring and improvement on colonoscopy, rectal mucous, colon sigmoid improved, no bleeding and clean mucous.  5-aminosalicylates is the first treatment in UC,  it also helps to achieve remission and prevent carcinoma development. UC is a disease that also causes extra-intestinal manifestation, so the treatment should be done holistically. Compliance and regular monitoring will help to improve the quality of life.